Regional spread and gross margin in the production of tobacco in the Republic of Macedonia - Peševski, Mile; Dragić, Živković; Filiposki, Blaže (Economics of Agriculture, 2010)
Based on the statistical data (2005-2009) the frst part of the paper analyses the areas under tobacco production and the tobacco production by regions in the Republic of Macedonia. Accordingly it was found that 86,7% of the total area, i.e. 85,3% of the total tobacco quantity is produced in the Pelagonia and South-east region. Total of 24 producers were surveyed in all 8 regions. The aim of the survey is to determine the scope and structure of the total income and variable costs, and than the gross margin and price. The authors fnd that the value of production ranges between 3. 538,3 EUR/ha in the Skopje region and 9. 034,3 EUR/ha in the Polog region. The same relationship is found in the variable costs, or on average 3. 982,3 EUR/ha, and individually range from 2591. 8 EUR/ha in Skopje region to 5. 199,0 EUR/ha in Polog region. Tobacco producers in the northeast region realize the lowest gross margin (1. 130,6 EUR/ha) while the highest (5. 780,7 EUR/ha) is found Polog region. At the same time, producers in the northeast region, produce tobacco at the lowest price (1,70 EUR/kg) and highest (2,65 EUR/kg) priced tobacco is produced in the easte region.